SELF-MANAGEMENT AND QUALITY OF LIFE AMONG CHRONIC KIDNEY DISEASE PATIENTS UNDERGOING HEMODIALYSIS - Sherli Amelia Putri Prasetya; Rif'atul Fani; Riki Ristanto (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Introduction: Chronic kidney disease is a progressive condition that requires long-term hemodialysis and can substantially affect patients’ quality of life. Effective self-management is essential to support patients in managing symptoms, adapting to treatment demands, and maintaining physical and mental well-being. Methods: A descriptive correlational design using a cross-sectional approach was used in this research. The participants were patients with CKD undergoing routine hemodialysis at a regional public hospital in Sidoarjo, Indonesia. A total of 194 respondents were recruited using purposive sampling. Self-management was assessed using the Hemodialysis Self-Management Instrument (HDSMI-18), and quality of life was calculated using the Kidney Disease Quality of Life (KDQoL-36) questionnaire. Univariate analysis with Spearman correlation tests used to analyzed data. Results: Self-care was significantly associated with symptom control (r = 0.190; p = 0.008), effects of kidney disease (r = 0.412; p < 0.001), disease burden (r = 0.322; p < 0.001), and mental quality of life (r = 0.497; p < 0.001). Problem solving was associated with effects of kidney disease (r = 0.220; p = 0.002) and mental quality of life (r = 0.158; p = 0.027). Emotional management was related to physical (r = 0.147; p = 0.041) and mental quality of life (r = 0.147; p = 0.040). Overall self-management was associated with effects of kidney disease (r = 0.296; p < 0.001), disease burden (r = 0.171; p = 0.017), and mental quality of life (r = 0.277; p < 0.001), while partnership showed no significant associations. Conclusions: Self-management related to quality of life among patients undergoing hemodialysis, with self-care showing the strongest and most consistent associations. These findings highlight the importance of strengthening self-management skills, particularly self-care, problem solving, and emotional regulation, to optimize quality of life in patients with CKD.